CHRONIC TOXICITY, ANTIDIABETIC AND HYPOLIPIDEMIC ACTIVITIES OF SPONDIAS MOMBIN L. (ANACARDIACEAE) ON ALLOXAN-INDUCED DIABETIC RATS - Gbolade, A.; Akinlolu, A.; Ekor, M.; Odewabi, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
S. mombin is traditionally used in Nigerian traditional medicine to treat diabetes in addition to its abortificient, anthelmintic and other biological activities. Based on preliminary investigation, the stem bark ethanolic extract was investigated for effects on hyperglycaemia, hyperlipidemia, liver and kidney functions, and toxicity to various body organs after chronic daily administration at 150 mg/kg and 400 mg/kg to alloxan-induced diabetic rats for 4 weeks. A significant decrease (P<0.05) in alloxan-induced hyperglycaemia attaining near normalization was accompanied by restoration of pancreatic beta cells, as well as significant diminution (P<0.05) in hyperlipidemia after 4 weeks of extract therapy. Weights of animals significantly increased (P<0.05) after the 3rd and 4th weeks when treated with both extract and chlorpropamide. Reversal of damage to brain and liver was significant (P<0.05) with the extract while the weights of other organs like lung, spleen, heart and kidney did not change significantly relative to diabetic control. Moreover, while the standard antidiabetic drug was significantly hepatotoxic (P<0.05), levels of serum enzymes like alanine aminotransferase and aspartate aminotransferase were unaltered in extract-treated animals. Both the extract and chlorpropamide significantly (P<0.05) reduced urea level in diabetic rats. Exceptions were lymphocyte and neutrophils. The extract did not show any significant difference in the haematological parameters. These data appear to justify the antidiabetic, hypolipidemic and protective potential for most organs by S. mombin, in traditional medicine.